Scheduled Optimal SDWSN Using Wireless Transfer of Power - Anand, C. (IRO Journal on Sustainable Wireless Systems, 2020)
Energy scarcity is one of the biggest threats faced by today's society because of the increasing demand for Wireless Sensor Networks. Wireless power transfer is one of the merging solutions that promise to address this energy scarcity and replenish the sensor nodes. In this method, dedicated energy transmitters are used to transfer energy to the sensor nodes. Moreover, Software-defined Wireless Sensor Networks (SDWSNs) have been proposed recently and are defined such that they are used to utilize the WSN resources to its maximum potential. The proposed methodology proposes a Wireless power transfer using SDWSN. We have designed a method to find the minimum energy transmitters by placing the energy transmitters in the node. A trade-off is made between fair distribution of energy and maximum energy charged in the network to place the energy transmitters. The proposed mechanism is defines a utility function in order to increase fairness and total energy charged. The goal is to decrease the energy consumed by the transmitters while retaining the charge of the sensor nodes. The simulation results illustrate the optimum efficiency of the proposed methodology with respect to energy consumption, number of tasks, number of energy transmitters, fairness and energy charged.
Keywords: wireless sensor networks; RF energy harvesting; optimization; optimal node placement